2018
DOI: 10.1007/s11748-018-0981-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of G472A allele of membrane bound catechol-O-methyltransferase gene with chronic post-sternotomy pain

Abstract: Chronic persistent surgical pain (CPSP) is a complex disease with strong genetic component. The studies on revealed association of mutations in membrane bound catechol-O-methyltransferase gene with CPSP were reported indifferent ethnic populations across the globe. We identify that one out of four patients who underwent sternotomy procedure showed CPSP even after 3 months of surgery. The Mb.COMT gene sequence analysis revealed of the four patients, three patients had no mutation in Mb.COMT gene, while in one p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Further we noticed that all these patients have silent mutations in which the change in nucleotide sequence does not alter amino acid codes, this condition may persuade in developing missense/nonsense mutations in future generations. This is the first study wherein we observed the impact of the COMT exon 4 novel mutations in patients showing CPSP even after 3 months with NRS scores ≥4 …”
mentioning
confidence: 80%
See 2 more Smart Citations
“…Further we noticed that all these patients have silent mutations in which the change in nucleotide sequence does not alter amino acid codes, this condition may persuade in developing missense/nonsense mutations in future generations. This is the first study wherein we observed the impact of the COMT exon 4 novel mutations in patients showing CPSP even after 3 months with NRS scores ≥4 …”
mentioning
confidence: 80%
“…Especially COMT mutated allele G472A (Val158Met) associated with chronic post‐surgical pain (CPSP) patients is reported in different ethnic population resulting in a less thermo stable enzyme with reduced activity . In this report we presenting the novel mutations p.(Arg128Ala) and the incidence of other genetic variations in exon 4 of COMT causing CPSP in sternotomy patients (Figure ).…”
mentioning
confidence: 89%
See 1 more Smart Citation